Peningkatan Hasil Belajar Pendidikan Pancasila Tema Jati Diri dan Lingkungan dengan Menggunakan Model Problem Based Learning Siswa Kelas V di SD Negeri 004 Samarinda Ilir - Laura Kristin; Iksam; Ulfah Maulidhya; Mustamiroh (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Pancasila Education is a subject that plays a crucial role in shaping students’ character and attitudes in accordance with the values of Pancasila. However, the learning outcomes of fifth-grade students on the topic My Identity and My Environment at SD Negeri 004 Samarinda Ilir were still relatively low. This condition was caused by a teacher-centered learning process in which students were less active, less motivated, and not accustomed to relating the learning material to real-life problems. This study aimed to improve students’ learning outcomes in Pancasila Education through the implementation of the Problem Based Learning (PBL) model. The research employed a Classroom Action Research design conducted in two cycles, consisting of planning, action, observation, and reflection stages. The research subjects were 22 fifth-grade students. Data collection techniques included observation of teacher and student activities, learning achievement tests, interviews, and documentation. The results showed that the implementation of the Problem Based Learning model increased both student activity and learning outcomes. The average score improved from 69.6% in Cycle I to 86.3% in Cycle II, with classical mastery reaching more than 85% of students achieving scores above the Minimum Learning Achievement Criteria (75). Based on these findings, it can be concluded that the Problem Based Learning model is effective in improving fifth-grade students’ learning outcomes in Pancasila Education at the elementary school level.